Molecular genetic characterization of Rusa (cervus timorensis) and sika (cervus nipon) deer Species in Malaysia - Khaledi, Kourosh Jome (2008)
The Malaysian livestock industry is an important component of the agricultural sector providing gainful employment and producing useful animal protein food to the population. Cattle, buffalo, goat, sheep and swine are the popular livestock in Malaysia. However, in recent years deer farming for meat, fur and velvet has become popular as well. Most of the farmed deer are of various species imported from different sources, such as Australia, New Zealand, Mauritius, Indonesia, New Caledonia, etc. The genetic background of these species and populations from different sources are unknown. This study was conducted to characterize two popular deer species in Malaysia, namely the rusa deer (Cervus timorensis) and the sika deer (Cervus nippon), using DNA microsatellite markers. The use of amelogenin gene primers for sexing of the rusa deer was also investigated. Random samples of 38 rusa deer from the Deer Breeding Unit of the University Research Park, Universiti Putra Malaysia, and 34 sika deer from Pusat Ternakan Haiwan, Batu Arang, were used in the study to determine and compare the genetic structures of the two deer species. One hundred and twenty five sets of microsatellite primer pairs, which had been reported to have successfully detected variation in deer, cattle or sheep, were used in the initial screening. Thirty nine primer pairs produced clear and reproducible amplification products for rusa and 41 primer pairs for sika. Twenty one primer pairs were polymorphic for the pooled data. However, only nine microsatellite loci (23.08%) were polymorphic for rusa and 17 loci (41.46%) were polymorphic for sika. Of these, only five were common to both deer species (BMS789, BM888, BL4, BM3628 and NVHRT16). Of the monomorphic loci, 17 were common to both species. Among the 11 reindeer microsatellite loci screened, nine loci (81%) were amplified for the pooled data, but only four loci were common to both species. The two white-tailed deer microsatellite loci (L35582 and L35583) produced amplification in sika but only L35583 was amplified in rusa. The 17 common monomorphic loci and the nine polymorphic loci generated in total 53 and 40 microsatellite markers in the rusa and sika, respectively. Locus BM2113 was amplified exclusively in rusa (126 bp), and locus NVHRT34 was amplified only in sika (134 bp). These loci may be used as unique markers to distinguish the two deer species. The numbers of observed and effective alleles per polymorphic loci were 2 - 13 and 1.05 - 8.91 for rusa, and 2 - 8 and 1.16 - 5.98 alleles per locus for sika, respectively. The allele frequencies ranged from 0.01 to 0.97 for rusa, and 0.02 to 0.92 for sika. The sizes of the alleles at the polymorphic loci ranged from 116 to 389 bp in rusa, and 88 to 364 bp in sika. The mean numbers of effective alleles were 3.08±2.40 and 2.87±1.65 in rusa and sika, respectively. Six loci in rusa and three loci in sika exhibited rare alleles. The mean observed heterozygosity in the rusa and sika populations were 0.48 ± 0.35 and 0.51 ± 0.30, respectively. Seven polymorphic loci in rusa and 14 polymorphic loci in sika exhibited significant (P<0.01) deviations from Hardy-Weinberg equilibrium. The Hardy-Weinberg disequilibrium may be due to overlapping of generations and founder effect, especially in the sika deer population. The combined discrimination power (cDP) of the nine polymorphic loci in rusa was 0.99 and of the seventeen polymorphic loci in sika was 0.99, thus allowing individual identification. The inbreeding coefficient (FIS) was very low for the rusa population (0.06), but for the sika population it was 0.26. The mean value of FST was 0.67 for rusa and 0.47 for sika. The bottleneck analysis suggested that the rusa population did not experience any recent bottleneck, whereas the sika population had encountered a genetic bottleneck in the recent past. Evaluation of intra-interchromosomal linkage disequilibrium between the alleles suggested significant (P<0.05) linkage between 10 pairs of alleles in rusa and 12 pairs of alleles in sika. However, none of the allelic pairs were the same for the two species. The genetic distance within the rusa population was lower than that within the sika population (0.088 ± 0.001 vs. 0.184 ± 0.001). The genetic distance between rusa and sika was 0.35. No distinct clustering was observed for the rusa population. The sika population displayed two major clusters of 11 and 23 individuals. The larger cluster in turn had two subclusters. The above results show the rusa and sika populations to be genetically different from each other. High genetic variation exists in both the populations. This could be due to low inbreeding and no directional selection in these populations. Four amelogenin gene primer pairs were used to identify the sexes of the rusa deer. Three primer pairs, AMEL2, AMGX/Y and AMGX/Y2, exhibited similar banding patterns for the males and females. The primer pair SE47/48 generated one band for the females (269 bp) but three bands (223, 269 and 305 bp) for the males. Therefore, this primer pair is a reliable tool for the identification of the sexes in the rusa deer.